An Authentication Approach in a Distributed System Through Synergetic Computing - Jia-Jen Wang; Yaw-Chung Chen; Meng-Chang Chen (Computers)
A synergetic computing mechanism is proposed to authenticate the validity of event data in merchandise exchange applications. The events are handled by the proposed synergetic computing system which is composed of edge devices. Asteroid_Node_on_Duty (ANOD) acts like a supernode to take the duty of coordination. The computation performed by nodes in local area can reduce round-trip data propagation delay to distant data centers. Events with different risk levels are processed in parallel through different flows by using Chief chain (CC) and Telstar chain (TC) methods. Low-risk events are computed in edge nodes to form TC, which can be periodically integrated into CC that contains data of high-risk events. New authentication methods are proposed. The difficulty of authentication tasks is adjusted for different scenarios where lower difficulty in low-risk tasks may accelerate the process of validation. Authentication by a certain number of nodes is required so that the system may ensure the consistency of data. Participants in the system may need to register as members. The transaction processing speed on low-risk events may reach 25,000 TPS based on the assumption of certain member classes given that all of ANOD, and Asteroid_Node_of_Backup (ANB), Edge Cloud, and Core Cloud function normally.